Optimization of cultivation conditions for the production of bacterial phytase from enterobacter sakazakii ASUIA279 newly isolated from Malaysian maize root - Meor Hussin, Anis Shobirin; Abd. El Aziem, Farouk; Salleh, Hamzah; Ali, Abdul Manaf; Ideris, Aini (2009)
Due to several biological characteristics, bacterial phytases have considerable potential in commercial and environmental applications. Until now, there is no single phytase that is able to meet the diverse needs for all commercial and environmental applications. Phytase enzyme preparations have a wide range of applications in animal and human nutrition. The addition of phytase can improve the nutritional value of plant-based foods by enhancing protein digestibility and mineral availability through phytate hydrolysis during digestion in stomach or during food processing. The extra cellular production of Enterobacter sakazakii ASUIA279 previously isolated from Malaysian maize root was optimized using response surface methodology with full-factorial faced centered central composite design. Two steps of experiments were carried out to optimize the five most profound factors of the cultivation conditions in order to maximize the phytase production. Incubation temperature, initial pH of the media and percentage of rice bran supplemented in the media were optimized in Erlenmeyer flasks while agitation and aeration effect were further up in a bioreactor. This design reduced the number of actual experiment performed while allowing for possible interactions among the factors. The optimum combination of cultivation conditions for maximum phytase production were determined at incubation temperature which is 39.7°C, initial pH 7.1, rice bran percentage at 13.6%, 320 rpm of agitation and 0 vvm of aeration. The response surface model is a valuable tool for predicting and optimizing the cultivation conditions to maximize the phytase production. The results show that phytase production by E. ASUIA279 can be improved by controlling various factors simultaneously.